Impacts of peatland drainage on soil properties : a study of drainage effects on boreal peatlands in northern Sweden - Klaus, Frederika (SLU/Dept. of Forest Ecology and Management, 2022)
Peatlands cover approximately 3% of the terrestrial surface on Earth and perform several important ecosystem functions, such as carbon storage and water retention. During the late 19th and early 20th centuries, approximately 2 million hectares of peatlands in Sweden were drained to manage the land for forestry and agriculture. Peatland drainage has since become a more regulated practice, and several projects are underway to rewet drained peatlands to restore their important ecosystem functions. Though the rewetting of peatlands restores the saturated conditions, the effects of drainage on the chemical and physical properties of peat can potentially still have an impact on biogeochemical processes following restoration. The aim of this thesis is therefore to investigate the intermediate drainage period to identify its effects on several key peat properties. This project utilized data collected in 2020 from three drained and four natural peatlands in northern Sweden. Peat cores were collected to a depth of 50 cm, and the studied variables were dry bulk density, organic matter content, C:N ratio, carbon content, nitrogen content, δ 13C, and δ15N. Groundwater data recorded in 2021 was also included from four of the seven peatlands. The organic matter content and dry bulk density showed the most significant difference between the natural and drained peatlands. In both cases, these differences were primarily at 10-20 cm depth, where the drained peatlands had a higher bulk density and lower organic matter content than the natural. These patterns are indicative of drainage effects, as it enables greater compaction of the soil and increased decomposition rates. The C:N ratio, carbon content, nitrogen content, δ 13C, and δ 15N did not show a statistically significant difference between the natural and drained peatlands. The impact on dry bulk density has implications for peatland water retention and the loss of organic matter may affect carbon storage abilities. Impacts on carbon and nitrogen dynamics were less clear and warrant further study. As peatland rewetting initiatives are implemented, it is important to further our understanding of drainage impacts on peatlands in order to carry out successful and effective restoration projects.